Distal acupoint stimulation versus peri-incisional stimulation for postoperative pain in open abdominal surgery: a systematic review and implications for clinical practice - Juan Zhu; Qian Xu; Rong Zou; Wenzhong Wu; Xiaoqiu Wang; Yanyi Wang; Fangbing Ji; Zhen Zheng; Man Zheng (BMC, 2019)
Abstract Background Acute postoperative pain remains a major clinical problem that affects patient recovery. Distal acupoint and peri-incisional stimulation are both used for relieving acute postoperative pain in hospital. Our objective was to assess and compare the effects of distal and peri-incisional stimulation on postoperative pain in open abdominal surgery. Methods MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials and Chinese databases CNKI and Wanfangdata were searched to identify eligible randomized controlled trials. Intensity of postoperative pain, opioid consumption and related data were extracted and analyzed using a random effects model. Risk of bias was assessed. Subgroup analyses were conducted when data were enough. Results Thirty-five trials were included, in which 17 trials studied distal stimulation, another 17 trials studied peri-incisional stimulation and one studied the combination of the two approaches. No studies that directly compared the two approaches were identified. Subgroup analysis showed that both distal and peri-incisional stimulation significantly alleviated postoperative resting and movement pain from 4 h to 48 h after surgery by 6 to 25 mm on a 100 mm visual analogue scale. Peri-incisional stimulation showed a better reduction in postoperative opioid consumption. No studies compared the effects of the combined peri-incisional and distal stimulation with either mode alone. Overall the quality of evidence was moderate due to a lack of blinding in some studies, and unclear risk of allocation concealment. Conclusion Both distal and peri-incisional modes of stimulation were effective in reducing postoperative pain. Whether a combined peri-incisional stimulation and distal acupuncture has superior results requires further studies.